Processos oxidativos avançados na degradação de hormônios sexuais femininos: cinética, produtos e toxicidade - Perondi, Taise (2019)
Natural hormones, such as estrone (E1), 17β-estradiol (E2), estriol (E3), and synthetic, 17α-ethinyl estradiol (EE2) are often detected in wastewater and surface water, causing concern because of their toxicity aquatic life at extremely low levels. More specifically, these substances classified as Endocrine Disrupters cause alarming effects, such as: feminization, hermaphroditism and decreased fertility. Advanced Oxidative Processes (POAs) have been quite effective in removing these Endocrine Disruptors, as these pollutants persist in conventional treatments. However, in natural matrices, the transformation of hormones during these processes is still not well understood, especially, with respect to the intermediates generated and their toxicity. Thus, this study aimed to investigate the behavior of the hormones E1, E2, E3 and EE2 in photochemical degradation in surface water samples, with respect to kinetics, by-product identification and toxicity. In the first stage of this research the quantification of these hormones in the surface waters of the Cubatão-SC and Marmeleiro-PR Rivers was done. In the second step, the photochemical behavior of the hormones under ultraviolet irradiation (UVC, 254 nm) associated with oxidants (H2O2 or O3) or the photocatalyst (TiO2) was investigated to evaluate the degradation potential and transformation pathway in an environment aquatic. E1, E3 and EE2 were detected in the river waters samples, while E2 and EE2 were found in the waters of the river Marmeleiro. The degradation kinetics of E1, E2, E3 and EE2 (200 μg.L-1) were studied by means of liquid chromatography with mass spectrometry (CG-MS) and the results were adjusted to the kinetic model of pseudo first order. kinetic constants: kE1> kE2> kEE2> kE3. Several processing intermediates were identified by liquid chromatography with mass-time-of-flight (HPLC / TOF-MS) spectrometer in surface water samples, which were derived from the aromatic ring cleavage and addition of the hydroxyl radical. Many of the identified products were found for the first time in POA treatments. Most of them showed very toxic chronic toxicity (ChV) for a diversity of species, according to an estimate made by ECOSAR software, which confirms that these products may pose a risk to the environment. Most of them showed very toxic chronic toxicity (ChV) for a diversity of species, according to an estimate made by ECOSAR software, which confirms that these products may pose a risk to the environment. Acute toxicity tests using Vibrio fisheri bacteria were made after reactions with the hormone mixture and the UV / TiO2 treatment was the most toxic to bacteria. The results obtained in this study contribute to increase the knowledge about the presence of the hormones E1, E2, EE2 and E3 in Brazilian rivers. Moreover, to understand the photochemical behavior in the degradation of these hormones in environmental samples, it is believed that this is the the first time these by-products were confirmed in experiments on samples with actual surface water.